Crescimento, caracterização óptica e estrutural e estudo de pontos quânticos semicondutores de PbS e PbSe em matrizes Vítreas - Silva, Ricardo Souza da (2004)
lt was synthesized and characterized quantum dots (semiconductor nanocrystals) PbS and PbSe hosted in glasses. I lt was obtained optical absorption (OA), Photoluminescence (PL) and Microluminescence spectra. Both OA and PL bands dislocate for higher wavelength when submitted to thermal-treatment for time increasing, starting growing the PbS and PbSe quantum dots. PL spectra, obtained as a power and temperature function, showed a structure present in 1350 and 1400 nm range attributed to intrinsic defects in the nanocrystals. Microluminescence spectra, obtained as temperature function, show photon diffusion larger in the smallest quantum dots. Atomic Force Microscopic (AFM) images. obtained in glasses host with composites 4OSÍO2. 30Na2CO,3 . 4PbÜ2. IAI2O3 . 25B2O3 (mol%) + 2S (%wt), confirm the PbS quantum dots growing. The average size of PbS and PbSe quantum dots were estimated, through four-band envelope function model.